Analisis Daya Saing Kelapa Sawit Di Kabupaten Kampar - Nur Farita Rita (UNIVERSITAS LANCANG KUNING, 2021)
The research aimed to analyze the competitiveness condition (comparative advantage and competitive advantage) of oil palm plantation business in Kampar Regency and to create the strategy in terms of improving the competitiveness of oil palm fresh fruit bunch (FFB) in Kampar Regency. The research was conducted in Kampar Regency Riau Province, where the research locations were in Bangkinang Sub-district, Tapung Hulu Sub-district, Siak Hulu Sub-district, Kampa Sub-district and Kampar Kiri Sub-district. The research location was determined by considering the area of ​​oil palm production by observing the available data, the data analysis was conducted by using policy analysis matrix (PAM). The result showed that oil palm agribusiness for 18 years in Kampar Regency has gained financial profit as much as Rp. 450,821,662 per hectare and the economic profit as much as Rp 437,941,556 per hectare, and internationally competitive, it was indicated by the ratio of domestic resource (DRC) with the value of 0.31. In addition, it was financially competitive, indicated from the value of Private Cost Ratio that was 0.11. The combination impact of policy transfer from input and output tradable indicated that the effective protection coefficient (EPC) value of oil palm agribusiness was 1.04. The value depicted that overall not only the farmer but also the commodity system were protected with the value of 4%. In additon the value of profitability coefficient (PC) from oil palm agribusiness in Kampar Regency was 1.33. The value indicated the higher financial profit, it was 1.33 times more than the economic profit. Subsidy ratio to producers (SRP) which was the measurement of the combination of all occured transfer effects showed the value of 0.23 which meant the divergency between the financial profit and economic profi towards the oil palm agribusiness approximately around 23% from the gross profit. The PCR value was smaller than DRC value, therefore the oil palm agribusiness in Kampar Regency is still in need of Goverment Intervention. Keywords: Competitiveness, Oil Palm Commodity, Kampar Regency.